Morphological and pathogenic characterization of Fusarium oxysporum in lulo (Solanum spp.) - Anama, Yohana Patricia; Díaz, Ricardo; Duarte-Alvarado, David Esteban; Lagos-Burbano, Tulio Cesar (Revista de Ciencias Agrícolas, 2021)
Fusarium oxysporum is one of the most limiting fungal pathogens of lulo crop. To determine its pathogenicity, this work morphologically and pathogenically characterized F. oxysporum isolates from different lulo-growing municipalities of the Department of Nariño. Twenty isolates were evaluated through a completely randomized design with two factors and three replicates per treatment, including a control. The first factor corresponded to 20 isolates of F. oxysporum and the second to 10 lulo genotypes. The morphological characterization involved determining growth rate (GR), color (CO), mycelial type (MT), medium coloration (Mc), shape (Sh), size (S), number (N) of macroconidial (Ma) and microconidial (Mi) septa, presence of chlamydospores (PC), and chlamydospore shape (CS). Moreover, the pathogenic characterization was based on the incubation period (IP), absolute growth rate (AGR), disease severity (DS), disease incidence (I), and vascular discoloration (VD). The morphological characterization demonstrated that all isolates corresponded to F. oxysporum. For IP, genotype G1 showed the lowest average at 18 days. For AGR, genotype G2 had the lowest height increase at 0.05 cm.day-1. For DS, genotype G1 reached the highest severity level (level 9) and a disease incidence of 100%. This study provides the first report of the special form of F. oxysporum f. sp. quitoense in Nariño. Solanum hirtum, Solanum sessiliflorum, and Solanum estramonifolium were resistant to the isolates evaluated, demonstrating that wild species should be considered as sources of resistance for breeding programs aiming to obtain resistant commercial genotypes.